Mitotic index maximization with no effect on radiation-induced dicentric chromosome frequency - Takebayashi, Kai; Echizenya, Keito; Kameya, Yuki; Nakajima, Daichi; Nakayama, Ryo; Fujishima, Yohei; Goh, Valerie Swee Ting; Abe, Yu; Kasai, Kosuke; Anderson, Donovan A.; Blakely, William F.; Miura, Tomisato (International journal of radiation biology, 2023)
The dicentric chromosome (Dic) assay, which is the gold standard for biological dose assessment in radiation emergency medicine, requires an analysis of at least 500 lymphocyte metaphases or 100 Dic aberrations. Therefore, peripheral blood culture conditions able to obtain a high frequency of metaphases for efficient dose evaluation should be optimized. However, the type of blood cultures [i.e. whole blood (WB) or isolated peripheral blood mononuclear cell (PBMC)-culture] and blood volume differ between biodosimetry laboratories. The purpose of this study is to investigate the blood volume at which a high mitotic index (MI) is obtained in peripheral WB-culture and isolated PBMC-culture, and to examine the possible effect of blood volume on radiation-induced Dic frequency. Peripheral blood was collected from three healthy donors with their informed consent. The complete and differential blood counts were performed using an automated hematology analyzer. After blood count, peripheral blood was irradiated with 0 or 2 Gy X-ray. Blood was cultured with phytohemagglutinin (180 μg/ml) and demecolcine　(0.05 μg/ml) for 48 h. The MI and Dic frequency were analyzed in 5, 10, 15, 20, 25, and 30% WB-cultures and 0.6, 1.2, 1.8, 2.4, 3.0, 3.6, and 4.2 ml WB-equivalent PBMC-cultures. In WB-culture, MI showed the highest value (∼22%) in 5-15% WB-culture and then gradually decreased to ∼9% with 30% WB-culture. MI peaked at 36 and 31% in 1.8 and 2.4 ml-WB equivalent volumes for PMBC-cultures, respectively. MI progressively decreased as the amount of PBMCs increased. Although individual differences were observed in the MI values among the three subjects, all the subjects showed the same tendency and higher MI was seen in PBMC than WB-cultures. However, these factors had no significant impact on the yield of Dics. In all culture conditions, the estimated dose calculated based on the Dic frequency was equivalent to the absorbed dose of ex vivo X-ray-irradiated blood. While MI was affected by the blood culture type and the volume of cultured blood, Dic yield did not differ significantly between these conditions. These results could be used by relevant laboratories to optimize MI in certain circumstances.